Edukacyjne konteksty zastosowania muzyki popularnej - Skrzydlewski, Wojciech (Biuletyn Historii Wychowania, 2023)
The article presents selected issues concerning the educational contexts of the application of popular music. It focuses on the development of phonography from the mechanical to the modern form (virtual); popular music on television; ethnic sources of popular music, the non-commercial function of popular music; music at the service of ideas. The article takes into account several characteristics of the great number of educational applications of popular music. Some are linked to commemoration of the work of outstanding artists, honouring the beauty of countries and the natural environment, while others distinguish personalities, friendship and patriotism.